Speech Prosody 2020 2020
DOI: 10.21437/speechprosody.2020-40
|View full text |Cite
|
Sign up to set email alerts
|

The British English rising contour: an exception in read speech?

Abstract: This paper focuses on rising contours in English read speech. Our hypothesis is that they are very few in this particular speech style. This is confirmed by quantitative and qualitative analyses, conducted on a corpus of read speech by native English speakers with a standard British English accent. The main result of the quantitative analyses is that out of 1076 tone units, 82% (whether final or not) are uttered with a falling contour, which is much more than could be expected. The qualitative analyses consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
1
0
1
Order By: Relevance
“…A la suite et dans la lignée d'Anglish, le corpus AixOx (Herment et al, 2014b), fruit d'une collaboration entre le LPL et le laboratoire de phonétique de l'université d'Oxford, a vu le jour : comme Anglish, il regroupe les mêmes productions de lecture en anglais d'apprenants francophones de différents niveaux et de natifs anglophones, mais il propose aussi les productions équivalentes en français par des apprenants anglophones de différents niveaux et des natifs francophones. Il est ainsi possible de faire des comparaisons entre natifs et apprenants, entre les deux L1 et aussi d'étudier au plus près la L1 pour offrir des perspectives pédagogiques en L2 (Herment et al, 2020). AixOx est le plus grand sous-corpus d'une base de données plus large, OMPRODAT (Hirst et al, 2013), où l'on trouve des productions d'apprenants de quatre langues différentes (anglais, français, coréen et chinois).…”
Section: La Prosodie Dans Son Contexte Socialunclassified
“…A la suite et dans la lignée d'Anglish, le corpus AixOx (Herment et al, 2014b), fruit d'une collaboration entre le LPL et le laboratoire de phonétique de l'université d'Oxford, a vu le jour : comme Anglish, il regroupe les mêmes productions de lecture en anglais d'apprenants francophones de différents niveaux et de natifs anglophones, mais il propose aussi les productions équivalentes en français par des apprenants anglophones de différents niveaux et des natifs francophones. Il est ainsi possible de faire des comparaisons entre natifs et apprenants, entre les deux L1 et aussi d'étudier au plus près la L1 pour offrir des perspectives pédagogiques en L2 (Herment et al, 2020). AixOx est le plus grand sous-corpus d'une base de données plus large, OMPRODAT (Hirst et al, 2013), où l'on trouve des productions d'apprenants de quatre langues différentes (anglais, français, coréen et chinois).…”
Section: La Prosodie Dans Son Contexte Socialunclassified
“…To conclude, in our data, falls overwhelmingly dominate read speech in final and non-final tone units, which contradicts what is generally claimed. In another study (Herment et al, 2020) using both the ANGLISH corpus and the AixOx corpus, we analysed non-final contours in relation to syntactic structure. We examined the sequences of tones in read speech and found that the sequence fall+fall dominates in those data as well.…”
Section: Total Of Tones On Final (#) and Non-final (Non#) Intonation Unitsmentioning
confidence: 99%